Dimensi Ekonomi Dalam Kehidupan Nabi Adam (Tafsir Surat Thaha Ayat 117-119 Dan Surat Al-Baqarah Ayat 36) - Satia Bakti Wahidah; Ahmad Saepudin (STIES INDONESIA PURWAKARTA Dan MES PURWAKARTA, 2018)
The hikmah existence of Prophet Adam saw., as the first man who is created by Allah swt to be a caliph in the earth.. Allah create him as the first man with perfection of sense, and particular among other things, and live in heaven. So the concept of prosperity begins with a preliminary description in heaven. Syetan deceive him and ordered out of heaven,has appeared practice require of needs, hard work and the concept of prosperous as part of the economic dimension.